EARLY DIAGNOSIS OF DIC DEVELOPMENT INTO THE OVERT PHASE - Urge, Jan; Strojil, Jan (Biomedical papers, 2006)
Background: Disseminated intravascular coagulation (DIC) is a syndrome characterized by over-activation of intravascular coagulation, accompanied by consumption of coagulation factors. It is a pathologic systemic inflammatory response accompanied by release of coagulatory substances into the circulation.Aim: The aim of this paper is to emphasize the importance of early the early diagnosis of DIC and to present a case report of a successful early diagnosis and treatment.Method: A case report giving a detailed account of clinical and laboratory presentation of a case of DIC in a patient with sepsis. Relevant laboratory results and other tests are presented, treatment is described in detail.Conclusions: DIC remains an important and potentially life-threatening complication of severe disease and states. Early diagnosis is vital for the success of treatment, and in severely ill patients, the possibility of DIC should always be kept in mind in order to detect early signs and initiate treatment as soon as possible.
Keywords: Disseminated intravascular coagulation/Early diagnosis/Treatment